Skriti obrazi izključevanja - Lah, Tjaša (Pedagoška obzorja, 2025)
This article focuses on the issue of stigmatization, particularly of children with special needs (CSN) who attend primary school with adapted educational programs and receive additional expert assistance. The theoretical part outlines the fundamental forms of stigmatization, reflected through interconnected stereotypes, prejudices and discrimination – operating both on a systemic level (ableism) and on a direct, interpersonal level (disableism). The empirical part presents the findings of a study conducted among 120 eighth graders from primary schools in the Kozjansko and Obsotelje regions. The research focuses on students’ perceptions of the presence of stigmatization of CSN and students’ attitudes towards such peers, with particular attention to gender differences. The results reveal that students do recognize the presence of stigmatization of CSN in society, although this awareness appears only in relation to certain statements. Regarding individual traits commonly as-sociated with CSN, students’ responses were predominantly ambivalent. Students frequently described these children as unpredictable, struggling with behavioural self-regulation, and often lacking independence. Significant differences in stigmatization by gender are rarely observed. These inconclusive findings highlight the need for a systematic approach to addressing stigmatization within the school environment.
Keywords: children with special needs; discrimination; diskriminacija; eight graders; osmošolci; osnovna šola; otroci s posebnimi potrebami; primary school; stigmatisation; stigmatizacija